Safety of thrombolysis in stroke mimics: an observational cohort study from an urban teaching hospital in Sweden. Issue 10 (30th October 2017) - Kostulas, Nikolaos; Larsson, Martin; Kall, Tor-Bjorn; von Euler, Mia; Nathanson, David
Abstract : Objectives: Acute stroke management has changed dramatically over the recent years, where a timely assessment is driven by the expanding treatment options of acute ischaemic stroke. This increases the risk in treating non-stroke patients (stroke mimics) with a possibly hazardous intravenous thrombolysis treatment (IVT). Setting: Patients of the thrombolysis registry of Södersjukhuset AB, a secondary health centre in Stockholm, were retrospectively studied to determine complications and outcome after IVT in strokes and stroke mimics. Participants: Consecutively, 674 recruited patients from 1 January 2008 to 1 December 2013 were analysed regarding demographics and outcome at 3 months after onset of symptoms. Results: Ischaemic stroke was confirmed in 625 patients (93%), and 48 patients (7%) were stroke mimics. Patients with strokes were older than stroke mimics 72 (IQR: 64–81) vs 54 years (IQR 40–67), p<0.0001. Antihypertensive and antithrombotic treatment were more common in patients with stroke (p<0.0001 and p=0.006, respectively). National Institute of Health Stroke Scale did not differ at time of presentation. Excellent outcome defined as modified Rankin Scale score 0–1, at 3 months, was less common in stroke than in stroke mimics (50% vs 87.5%, p<0.0001). No stroke mimic had a symptomatic intracerebral haemorrhage. Age of less than 40 years may be a predictor for a patient to be a stroke mimic (OR: 8.7, 95% CI: 3.2 to 24.0, p<0.0001). Conclusions: Stroke mimics receiving IVT had a more favourable outcome compared with patients with stroke, and showed no haemorrhagic complications. Age below 40 years may be a predictor for stroke mimics.